McDowell and the Contents of Intuition. (21st July 2019) - Browning, Jacob
Abstract: In Mind and World, John McDowell provided an influential account of how perceptual experience makes knowledge of the world possible. He recommended a view he called "conceptualism", according to which concepts are intimately involved in perception and there is no non‐conceptual content. In response to criticisms of this view (especially those from Charles Travis), McDowell has more recently proposed a revised account that distinguishes between two kinds of representation: the passive non‐propositional contents of perceptual experience – what he now calls "intuitional content" – and the propositional contents of judgment – what he now calls "discursive content." In this paper, I criticize McDowell's account of intuitional content. I argue that he equivocates between two different notions of intuitional content. These views propose different, and incompatible, ways of understanding how a perceiver makes a judgment based on perceptual experience. This is because these two views result from an underlying indeterminacy as to what, if anything, McDowell now means by "conceptual" when he makes claims that intuitional content is conceptual.